An instrumental case study examining the introduction and dissemination of the Baby Friendly Health Initiative in Australia: Participants' perspectives. Issue 3 (June 2018) - Atchan, Marjorie; Davis, Deborah; Foureur, Maralyn
Abstract: Background: Australia experiences high breastfeeding initiation but low duration rates. UNICEF introduced the global breastfeeding strategy, the Baby-Friendly Hospital Initiative, to Australia in 1992, transferring governance to the Australian College of Midwives (ACM) in 1995. In 2017 23% of facilities were registered as 'baby-friendly' accredited. Aim: To examine the introduction and dissemination of the Baby-friendly Hospital Initiative into the Australian national setting. Methods: An instrumental case study was conducted containing two components: analysis of historical documents pertaining to the Initiative and participant's interviews, reported here. A purposive sampling strategy identified 14 participants from UNICEF, ACM, maternity and community health services, the Australian government and volunteer organisations who took part in in-depth interviews. Thematic analysis explored participants' perceptions of factors influencing the uptake and future of the since renamed Baby Friendly Health Initiative (BFHI) and accreditation programme, BFHI Australia. Two broad categories, enablers and barriers, guided the interviews and analysis. Findings: Participants revealed a positive perception of the BFHI whilst identifying that its interpretation and expansion in Australia had been negatively influenced by intangible government support and suboptimal capacity building. BFHI's advocacy agenda competed with BFHI Australia's need for financial viability. Widespread stakeholder collaboration and tangible political endorsement was seen as a way to move the strategy forward. Conclusion: Dissemination of BFHI Australia is hampered by multi-level systems issues. Prioritisation, stakeholder collaboration and adequate resourcing of the BFHI is required to create a supportive and enabling environment for Australian women to determine and practice their preferred infant feeding method.